2015
DOI: 10.1021/acs.nanolett.5b03922
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced below Bandgap Photoconductive Terahertz Generation and Detection

Abstract: We use plasmon enhancement to achieve terahertz (THz) photoconductive switches that combine the benefits of low-temperature grown GaAs with mature 1.5 μm femtosecond lasers operating below the bandgap. These below bandgap plasmon-enhanced photoconductive receivers and sources significantly outperform commercial devices based on InGaAs, both in terms of bandwidth and power, even though they operate well below saturation. This paves the way for high-performance low-cost portable systems to enable emerging THz ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…Numerous researchers have shown that on of the most effective implementation of dipole NAs in the THz photoconductive antennas and photomixers are arrays of metal dipoles whose length is of the order of the gap size between the electrodes. Arrays of dipole plasmonic NAs have received the name of plasmonic gratings or plasmonic nanorod gratings .…”
Section: Hybrid Photoconductive Thz Antennasmentioning
confidence: 99%
“…Numerous researchers have shown that on of the most effective implementation of dipole NAs in the THz photoconductive antennas and photomixers are arrays of metal dipoles whose length is of the order of the gap size between the electrodes. Arrays of dipole plasmonic NAs have received the name of plasmonic gratings or plasmonic nanorod gratings .…”
Section: Hybrid Photoconductive Thz Antennasmentioning
confidence: 99%
“…This is an advantage when considering practical implementation of THz PCA-based systems as 1.55-μm wavelength pulsed laser systems can be fully fiber based without consideration of dispersion effects. Although generation and detection of THz pulses in LT-GaAs PCAs has been demonstrated using 1.55-μm optical pulses, 113,114 a significant reduction in performance has been observed as compared to 800-nm excitation. This is mainly due to the lower absorption efficiency of LT-GaAs at 1.55 μm, since absorption at this sub-bandgap wavelength requires interband transitions to excite carriers to the conduction band, as illustrated in Fig.…”
Section: Indium Gallium Arsenidementioning
confidence: 99%
“…7 [Fig. 1 114 Therefore, materials with bandgaps at or below 0.8 eV have been sought out for use with 1.55-μm fiber laser systems.…”
Section: Indium Gallium Arsenidementioning
confidence: 99%
“…Most of these compact lasers operate at energies below the bandgap of the most popular ultrafast material, low-temperature grown GaAs (LT-GaAs). To make such compact systems viable, several approaches have been developed, including the use of LT-InGaAs/InAlAs multilayer structures, 16 GaBiAs-based substrates, 17 two-photon absorption enhancement with plasmonic nanostructures, 18 and the use of the above mentioned QD-based photoconductive devices. 6,9 For efficient THz generation, short carrier lifetimes are an important material property for PCAs in both the pulsed and CW pumping conditions.…”
Section: Introductionmentioning
confidence: 99%